PREPARATION OF CHITOSAN-GOLD NANOPARTICLES: PART 1 (OF 2). EFFECT OF REDUCING TECHNIQUE - Adlim Adlim; Mohamad Abu Bakar (Universitas Gadjah Mada, 2008)
Chitosan-stabilized gold nanoparticles were synthesized in aqueous formic acid, citric, or acetic acid with and without chitosan as the stabilizer. Refluxing in methanol, addition of hydrazine or sodium borohydride, photo-irradiation were employed as the reducing agents & reduction technique of gold ions. Dispersed particles of chitosan-stabilized gold were obtained in aqueous acetic acid-methanol solution. The chitosan-stabilized gold colloids (chi-Au) were dispersed and the particle size were in range of 9-30 nm, some of which were crystalline with various shapes. Chi-Au prepared with hydrazine as the reducing agent resulted in large and aggregated particles. The finest and dispersed chi-Au particles were obtained if NaBH4 was used as the reducing agent and the diameters could be controlled within 2.2-2.3 nm.